Bromine, arsenic, cadmium, and lead in several key food groups: an assessment of relative risk. Issue 15 (8th December 2018) - Ventura, Marta; Cardoso, Carlos; Bandarra, Narcisa Maria; Delgado, Inês; Coelho, Inês; Gueifão, Sandra; Ribeiro, Mariana; Costa, Maria Helena; Castanheira, Isabel
ABSTRACT: This study endeavoured to provide an overview of the bromine, Br, arsenic (As, a metalloid) and metal (cadmium, Cd, and lead, Pb) relative risk associated with the consumption of relevant food groups (lean fish, fatty fish, bivalves, cephalopods, fresh fruit, dried fruit, and green vegetables) in Portugal. Though As, Cd, and Pb have been frequently studied, a comprehensive overview applying the same state-of-the-art methodology to a wide array of foods is missing. Besides, there is a large deficit of content information and risk assessment studies on Br. Thus, it is important to apply a mathematically realistic and innovative methodology (extreme value theory) to recent and accurate databases for the aforementioned food groups and elements. Best fits to Br, As (total), Cd, and Pb concentrations were attained through different functions, ranging from the normal distribution to the Weibull distribution. A semi-probabilistic risk assessment approach on the basis of four alternative scenarios (one monthly meal; one weekly meal; three weekly meals; one daily meal) showed low relative risk regarding Br and Pb in the selected food groups, including bivalves, which contained the highest Br and Pb contents. With respect to total As, high relative risk values were calculated for seafood, but it should be emphasized that this As is overwhelmingly organic, thus presenting low risk. For Cd, substantial relative risk associated with bivalves' and cephalopods' consumption, particularly with one or more weekly meal(s), was found. However, the current study enables us to compare between the relative risk of the studied food groups and scenarios, and other studies encompassing the whole diet and following long-term dietary patterns are needed for the assessment of absolute risk.